A collaborative public health approach to clubfoot intervention in 10 low-income and middle-income countries: 2-year outcomes and lessons learnt. - Owen, R; Penny, J; Mayo, A; Morcuende, J; Lavy, C (2012)
Untreated clubfoot has been acknowledged as a public health problem in low-income countries. In 2007-2009, a 10-country initiative was implemented by a collaboration of nongovernmental organizations and Ministries of Health to establish and strengthen national programmes for management of clubfoot using the Ponseti technique. Independent evaluation used quantitative data on programme outcomes and qualitative data from service providers and users. Overall, 110 clubfoot clinics were established, 634 practitioners were trained and 7705 children were enrolled for treatment. The public health model of establishing services for clubfoot on a national level was found to be successful in the majority of countries included.